A PbWO4-based Neutral Particle Spectrometer in Hall C at 12 GeV JLab. (13th February 2015) - ,; ,
Abstract: The Neutral Particle Spectrometer is a standalone electromagnetic calorimeter capable of detecting high energy photons from, for instance, DVCS or π 0 decay with good energy and spatial resolution in a high rate environment. It can be used together with the Hall C high-momentum spectrometers for a suite of experiments with the underlying scientific objective of studying quark dynamics through exclusive and semi-inclusive reactions.